2016
DOI: 10.3390/pathogens5040062
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Type I Restriction–Modification Systems in Streptococcus suis: An Outlook

Abstract: Streptococcus suis is a porcine commensal and pathogen with zoonotic potential. We recently identified a novel Type I restriction–modification (R–M) system in a zoonotic S. suis clone which has emerged in the Netherlands. Here, we describe the DNA inversions in the specificity subunit of this system in S. suis serotype 2, clonal complex 20 and explain the absence of domain movement by the absence of repeats. In addition, we identified a core Type I R–M system present in 95% of the isolates and found an associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…This not only confirmed the sequence recognized and methylated by ModS2, but also showed that the same allele has the same specificity in different strains of S. suis , and therefore is highly likely to regulate the same phasevarion. The LSS66 methylome demonstrated the presence of two Type I motifs in this strain (Table 3 ), which we predict to be the sequence specificities of the two non-phase-variable Type I loci previously reported to be present in all strains of S. suis ( 37 ), but we cannot confidently assign these signatures to particular methyltransferases without significant additional analysis, which is outside the scope of the current work. An examination of REBASE ( 41 ) shows that these two Type I motifs have not previously been reported.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…This not only confirmed the sequence recognized and methylated by ModS2, but also showed that the same allele has the same specificity in different strains of S. suis , and therefore is highly likely to regulate the same phasevarion. The LSS66 methylome demonstrated the presence of two Type I motifs in this strain (Table 3 ), which we predict to be the sequence specificities of the two non-phase-variable Type I loci previously reported to be present in all strains of S. suis ( 37 ), but we cannot confidently assign these signatures to particular methyltransferases without significant additional analysis, which is outside the scope of the current work. An examination of REBASE ( 41 ) shows that these two Type I motifs have not previously been reported.…”
Section: Resultsmentioning
confidence: 74%
“…Our examination of genome sequences of S. suis also demonstrated the presence of two additional Type I R-M loci (YYK_03085-YYK_03100 and YYK_07615-YYK_07625 in strain S735). Previous in depth analysis of Type I R-M systems in S. suis has shown that homologues of these loci are distributed across the majority of S. suis strains ( 37 ). This work also demonstrated the presence of the phase-variable Type I R-M system studied here, but did not show phase-variation within the population of an individual strain as we have.…”
Section: Resultsmentioning
confidence: 99%
“…First of all, a disease-associated marker was described, which is predicted to be a copper-exporting ATPase (SSU207) potentially playing an essential role in copper homeostasis in Gram-positive and -negative bacterial pathogens [ 31 , 32 ]. The second proposed disease-associated marker is annotated as type I restriction-modification (RM) system S protein (SSU1589) in S. suis strain P1/7 (GenBank accession number NC_012925.1) and is supposed to be implicated in the defense of host bacteria [ 33 ]. The third genetic marker is thought to be non-disease-associated and the corresponding protein is suggested to be a putative sugar ATP-binding cassette (ABC) transporter (SSUST30534).…”
Section: Introductionmentioning
confidence: 99%
“…The findings indicated these two hsdS may each has a unique regulatory mechanism that needs to be elucidated. Additionally, the systematic study of the regulation of virulence in the Type I RM system in SS2 has not previously been performed (Willemse and Schultsz, 2016 ), and that type of systematic study is the goal of this research.…”
Section: Introductionmentioning
confidence: 99%